Arsenene Nanodots with Selective Killing Effects and their Low‐Dose Combination with ß‐Elemene for Cancer Therapy. Issue 37 (26th July 2021) - Liu, Chuang; Sun, Shan; Feng, Qiang; Wu, Gongwei; Wu, Yiting; Kong, Na; Yu, Zhangsen; Yao, Junlie; Zhang, Xingcai; Chen, Wei; Tang, Zhongmin; Xiao, Yufen; et al.
Abstract: Arsenical drugs have achieved hallmark success in treating patients with acute promyelocytic leukemia, but expanding their clinical utility to solid tumors has proven difficult with the contradiction between the therapeutic efficacy and the systemic toxicity. Here, leveraging efforts from materials science, biocompatible PEGylated arsenene nanodots (AsNDs@PEG) with high monoelemental arsenic purity that can selectively and effectively treat solid tumors are synthesized. The intrinsic selective killing effect of AsNDs@PEG is closely related to high oxidative stress in tumor cells, which leads to an activated valence‐change of arsenic (from less toxic As 0 to severely toxic oxidation states), followed by decreased superoxide dismutase activity and massive reactive oxygen species (ROS) production. These effects occur selectively within cancer cells, causing mitochondrial damage, cell‐cycle arrest, and DNA damage. Moreover, AsNDs@PEG when applied in a multi‐drug combination strategy with β‐elemene, a plant‐derived anticancer drug, achieves synergistic antitumor outcomes, and its newly discovered on‐demand photothermal properties facilitate the elimination of the tumors without recurrence, potentially further expanding its clinical utility. In line of the practicability for a large‐scale fabrication and negligible systemic toxicity of AsNDs@PEG (even at high doses and with repetitive administration), a new‐concept arsenical drug with high therapeutic efficacy for selective solid tumor therapy is provided. Abstract : PEGylated arsenene nanodots (AsNDs@PEG) with high monoelemental arsenic purity and negligible systemic toxicity are identified as a new‐concept arsenical drug for selectively treating solid tumors through the valence‐change of arsenic to generate toxic oxidation states and on‐demand photothermal therapy. This work can encourage a fast‐paced clinical translation of arsenene for tumor treatments with potentially low attrition rates.